Evaluasi Website Repositori Institusi Universitas Surabaya - Amirul Ulum (IAIN Ponorogo, 2015)
The development of institutional repositories (IRs) in Indonesia within the broader framework of open access has significant impact on preserving intellectual capital and scholarly communication. Institutional repositories play a fundamental role in centralizing, preserving, and making accessible institution’s intellectual capital. Evaluation of the system is to determine the functionality the system to meet the users need. Using a descriptive analysis this study wants to evaluate institutional repositories of University of Surabaya. The result is usefull for institution to develop the repository systems.